Inherent impurities in 3D-printed electrodes are responsible for catalysis towards water splitting. Issue 3 (2nd January 2020) - Browne, Michelle P.; Urbanova, Veronika; Plutnar, Jan; Novotný, Filip; Pumera, Martin
Abstract : Researchers should be cautious about the presence of metal impurities in commercial conductive filaments and its crucial effect on O2 based electrocatalysis, which is altered depending on the post 3D-printing treatment. Abstract : 3D-printing is at the forefront of electrochemical energy research as it allows for rapid prototyping and remote on-demand fabrication of energy devices. In recent years, a commercially available 3D-printing graphene/polylactic acid (PLA) filament has been extensively utilised to fabricate electrodes for electrochemical applications. However, it has been reported that this commercial filament and hence the electrodes contain inherent impurities. Herein, these 3D-printed electrodes that contain such impurities are tailored as catalysts for the hydrogen evolution reaction (HER) and the photoelectrochemical (PEC) water oxidation reaction depending on the post 3D-printing treatment ( i.e. solvent or thermal based). Our results show that the thermally treated 3D-printed electrode has superior HER and PEC water oxidation properties compared to the bare and the solvent treated 3D-printed electrodes. The optimum performance of the thermally treated 3D-printed graphene/PLA electrode for the HER is linked to the presence of Fe and Ti impurities and the low carbon to oxygen ratio content. Additionally, for the PEC water oxidation, the increased performance for the same electrode is linked to the presence of TiO2 on the electrode surface. Hence, researchers in this field should be cautious about the presence of metal impurities in this commercial graphene/PLA filament and its crucial effect on electrocatalysis.